Peran Kesamaptaan dalam Meningkatkan Konsentrasi dan Motivasi Belajar Siswa di SD Negeri 091641 Bandar Tinggi - Wisuda Pramarta Lubis; Zamaluddin Sembiring (ARZUSIN, 2025)
Concentration and learning motivation are two crucial factors influencing student success in the educational process, particularly at the elementary school level. However, various obstacles such as physical fatigue, lack of physical activity, and learning boredom often reduce the quality of learning. This study aims to investigate the role of physical fitness activities in enhancing students’ concentration and learning motivation at SD Negeri 091641 Bandar Tinggi. A quantitative descriptive approach was employed, with data collected through observations, questionnaires, and interviews involving students and classroom teachers regularly participating in physical fitness activities. The results demonstrate a positive and significant relationship between the implementation of physical fitness activities and improvements in students’ concentration and learning motivation. The average concentration score increased from 68.25 to 78.90, and the learning motivation score rose from 70.40 to 82.15 following consistent participation in physical fitness programs. A paired sample t-test yielded a p-value of 0.000, indicating a significant difference before and after the program. Qualitative findings from interviews corroborate the quantitative data, showing that students active in physical fitness tend to be more alert, disciplined, engaged, and quicker to grasp lessons. In conclusion, the consistent implementation of physical fitness programs is effective in optimally preparing students mentally and physically for learning and can serve as a supportive strategy for academic success in elementary schools.